Southwest Research-Extension Center, Field Day 2008 (Kansas Agricultural Experiment Station Research Reports, 2008)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: SRP997; 2008; crops; tillage; irrigation; weed science; insect control